Survey on effective gamification elements for enhancing junior high students' English proficiency - Rosyidah, Umniyah Juman; Suharyadi, Suharyadi; Ivone, Fransisca Maria (Journal of English Language Teaching Innovations and Materials (Jeltim), 2024)
Gamification is one of the strategies widely applied by junior high school teachers in English language learning within their classrooms. However, the implementation of gamification thus far only focused on incorporating all gamification elements without considering which specific elements have the greatest impact on improving students' English proficiency. To fill this gap, this research is conducted to discover the gamification elements that can optimally increase English proficiency. Using survey method, this research involves 250 respondents from junior high school students in Kota Malang who have an experience in gamification strategies. The results show that gamification elements cannot increase students"™ English proficiency when implemented individually; while all involved gamification elements simultaneously affect the English proficiency. Therefore, to improve English proficiency, teachers should integrate all gamification elements within their instructional strategies. Because of its limitation, future research that involves respondents from different areas and school types needs to be conducted to provide a broader understanding of how these elements perform in various contexts.